Canadian Association of Gastroenterology Consensus Guidelines on Safety and Quality Indicators in Endoscopy. (2012) - Armstrong, David; Barkun, Alan; Bridges, Ron; Carter, Rose; de Gara, Chris; Dubé, Catherine; Enns, Robert; Hollingworth, Roger; MacIntosh, Donald; Borgaonkar, Mark; Forget, Sylviane; Leontiadis, Grigorios; et al.
Abstract : Several organizations worldwide have developed procedure-based guidelines and/or position statements regarding various aspects of quality and safety indicators, and credentialing for endoscopy. Although important, they do not specifically address patient needs or provide a framework for their adoption in the context of endoscopy services. The consensus guidelines reported in this article, however, aimed to identify processes and indicators relevant to the provision of high-quality endoscopy services that will support ongoing quality improvement across many jurisdictions, specifically in the areas of ethics, facility standards and policies, quality assurance, training and education, reporting standards and patient perceptions. Abstract : BACKGROUND: Increasing use of gastrointestinal endoscopy, particularly for colorectal cancer screening, and increasing emphasis on health care quality, highlight the need for clearly defined, evidence-based processes to support quality improvement in endoscopy. OBJECTIVE: To identify processes and indicators of quality and safety relevant to high-quality endoscopy service delivery. METHODS: A multidisciplinary group of 35 voting participants developed recommendation statements and performance indicators. Systematic literature searches generated 50 initial statements that were revised iteratively following a modified Delphi approach using a web-based evaluation and voting tool. Statement development and evidence evaluation followed the AGREE (Appraisal of Guidelines, REsearch and Evaluation) and GRADE (Grading of Recommendations, Assessment, Development and Evaluation) guidelines. At the consensus conference, participants voted anonymously on all statements using a 6-point scale. Subsequent web-based voting evaluated recommendations for specific, individual quality indicators, safety indicators and mandatory endoscopy reporting fields. Consensus was defined a priori as agreement by 80% of participants. RESULTS: Consensus was reached on 23 recommendation statements addressing the following: ethics (statement 1: agreement 100%), facility standards and policies (statements 2 to 9: 90% to 100%), qual: 97% to 100%) and patient perceptions ( statements 22 and 23: 100%). Additionally, 18 quality indicators (agreement 83% to 100%), 20 safety indicators (agreement 77% to 100%) and 23 recommended endoscopy-reporting elements (agreement 91% to 100%) were identified. DISCUSSION: The consensus process identified a clear need for high-quality clinical and outcomes research to support quality improvement in the delivery of endoscopy services. CONCLUSIONS: The guidelines support quality improvement in endoscopy by providing explicit recommendations on systematic monitoring, assessment and modification of endoscopy service delivery to yield benefits for all patients affected by the practice of gastrointestinal endoscopy.